PENGARUH LATAR BELAKANG PENDIDIKAN DAN KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI KCP BANK MUAMALAT KOLAKA - Sulkifli AR; Dirwan Dirwan (Jurnal Ekonomi Bisnis Syariah, 2019)
Influence of Educational Background and Ability on the Performance of Muamalat Bank Employees in the Kolaka Sub-Branch Office. The development of Islamic Banks at this time is very rapid, of course very encouraging, however, the development of Islamic Banks in the last three years has slowed while the number of manpower is increasing from year to year, so it can be assumed that the quality of human resources is currently lacking quality in developing banking Sharia. The formulation of the problem in this study, how does the influence of educational background and work ability on the performance of employees of Muamalat Bank Sub-Branch Office Kolaka ?. The purpose of this study was to determine the effect of educational background and work ability on the performance of Muamalat Bank employees at the Kolaka Sub-Branch Office. The method in this study uses quantitative research methods with several stages, namely determining variables, population & samples, data & data sources, data collection, instruments, and data analysis techniques. The results of this study are that educational background has no effect on performance, while work ability has an influence on the performance of employees of Muamalat Bank Sub-Branch Office Kolaka